2022
DOI: 10.1002/cam4.4846
|View full text |Cite
|
Sign up to set email alerts
|

Identifying tumor antigens and immuno‐subtyping in colon adenocarcinoma to facilitate the development of mRNA vaccine

Abstract: The mRNA vaccine has provided a promising approach for cancer immunotherapies. However, only a few mRNA vaccines have been developed against colon adenocarcinoma (COAD). Screening potential targets for mRNA vaccines from numerous candidates is a substantial challenge. Considering the tumor heterogeneity, only a subset of patients might respond to vaccinations. This study was conducted to identify potential candidates for mRNA vaccines, and distinguish appropriate subgroups of COAD patients for vaccination. A t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…As COAD develops and progresses, these antigens play an important role in their direct presentation to CD8 + T cells to induce an immune response upon lymphocyte infiltration. The potential of these candidate genes for mRNA vaccine development is supported by previous reports, although they have yet to be functionally validated [ 39 ]. This study is the first to screen for the potential antigens IL1B and BAX for the development of mRNA vaccines to treat patients with COAD.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…As COAD develops and progresses, these antigens play an important role in their direct presentation to CD8 + T cells to induce an immune response upon lymphocyte infiltration. The potential of these candidate genes for mRNA vaccine development is supported by previous reports, although they have yet to be functionally validated [ 39 ]. This study is the first to screen for the potential antigens IL1B and BAX for the development of mRNA vaccines to treat patients with COAD.…”
Section: Discussionmentioning
confidence: 84%
“…mRNA vaccine development is a significant challenge. The tumors of different patients exhibit varying genetic and molecular characteristics, which complicates the development of vaccines targeting specific tumor antigens [ 39 ]. Immune suppressive factors within the tumor microenvironment may affect the efficacy of mRNA vaccines [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…mRNA vaccines against colon adenocarcinoma are limited. A significant difficulty is sorting through the several vaccine candidates to identify possible mRNA vaccines that may be suitable for a specific type of cancer ( 145 ). Thrombospondin 2, follistatin like 3, troponin T1, biglycan, collagen triple helix repeat containing 1 and NADPH oxidase 4 are among the targeted antigens that Liu et al ( 139 ) identified as potential mRNA vaccine candidates.…”
Section: Applications Of Mrna Vaccines In Various Tumorsmentioning
confidence: 99%